2017
DOI: 10.1002/jlcr.3540
|View full text |Cite
|
Sign up to set email alerts
|

A modification to improve the reliability of [11C]CN production in the GE radiochemistry system

Abstract: We report herein a modification to a component of the GE radiochemistry system that increases the yield and reliability of [ C]CN production from [ C]carbon dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…[22,23] The fully automated [ 11 C]HCN production system is also commercially available. The Process Cabinet of the GE radiochemistry system is such a selection of choice, and the minor modification for supplying [ 11 C]HCN with increased production yield was reported in 2017 by David C. Labaree et al [24]…”
Section: [ 11 C]hcn Productionmentioning
confidence: 99%
“…[22,23] The fully automated [ 11 C]HCN production system is also commercially available. The Process Cabinet of the GE radiochemistry system is such a selection of choice, and the minor modification for supplying [ 11 C]HCN with increased production yield was reported in 2017 by David C. Labaree et al [24]…”
Section: [ 11 C]hcn Productionmentioning
confidence: 99%
“…[ 11 C]MTP38 was synthesized using [ 11 C]hydrogen cyanide ([ 11 C]HCN) from [ 11 C]CO 2 , which was generated by the 14 N(p,α) 11 C nuclear reaction using a cyclotron 1 . [ 11 C]HCN is a useful radioactive agent for synthesizing 11 C‐labeling PET imaging tracers 3–7 . The two‐step automated production of [ 11 C]HCN from [ 11 C]CO 2 was developed by Iwata et al, 8 and we recently modified it in an automated 11 C‐labeling synthesizer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…1 [ 11 C]HCN is a useful radioactive agent for synthesizing 11 C-labeling PET imaging tracers. [3][4][5][6][7] The two-step automated production of [ 11 C]HCN from [ 11 C]CO 2 was developed by Iwata et al, 8 and we recently modified it in an automated 11 C-labeling synthesizer. 9 For the fully automated production of [ 11 C]MTP38 routinely and efficiently for clinical applications, we determined the radiosynthesis procedure of [ 11 C]MTP38 via [ 11 C]HCN using the 11 C-labeling synthesizer.…”
mentioning
confidence: 99%
“…PET scans to check the kinetics of [ 11 C]5 in the whole body of mice suggested that [ 11 C]5 spreads rapidly into the brain, heart, and lungs and then accumulates in the small intestine. To evaluate the performance of CuImediated 11 C-cyanation reaction, bromobenzene (6a) was selected as the model compound; however, it failed. Therefore, optimization of the reaction conditions has been performed, and consequently, the addition of K 2 CO 3 and prolonging the reaction time improved the radiochemical yield about double.…”
mentioning
confidence: 99%
“…With this improved method, CuI-mediated 11 C-cyanation of various (hetero) aromatic bromides was performed to exhibit the tolerance of most functional groups and to provide 11 C-cyanated products in good to moderate radiochemical yields. Positron emission tomography (PET) is an attractive method for visualizing the dynamics of radiopharmaceuticals labeled with positron-emitting radionuclides in vivo.…”
mentioning
confidence: 99%